Comparing the effectiveness of using three different re-mineralizing pastes on remineralisation of artificially induced white spot lesion - Shahad S Rahee; Rasha H Jehad (College of Dentistry/ University of Baghdad, 2023)
Background: This study aimed to compare the surface microhardness (MH) and mineral content of white spot lesions(WSLs) after using bioactive glass (BAG)casein phosphopep-tides-amorphous calcium phosphate(CPP-ACP),and nanohydroxyapatite(Nano-HAP) under pHcycling. Material and method:18 sound maxillary first premolar were used for the study.10 were selected for the vickers microhardness test, For Energy-dispersive X-ray spectroscopy analysis (EDX), the remaining 8 premolar teeth were used, 40 sections of enamel blocks (Four from each tooth) were produced from the middle part of the buccal and palatal surfaces of teeth for MH test while 48 sections of enamel blocks (Six from each tooth) were produced for EDX analysis. Enamel slabs were divided into four groups: control group that preserved in DDW, Nano-HAP, CPP-ACP and BAG group, then were demineralised using 0.1 M lactic acid and 8 wt.% carboxymethylcellulose gel to create artificial WSL. The speci-mens were subjected to a pH cycling regime for 20 days. The remineralisation potential of the specimens was studied by evaluating the surface MH, calcium (Ca), and phosphrous (P) at different stages: baseline, after production of WSLs, and after treatment with different ma-terials. The gathered data were statistically analyzed using repeated measures one-way ANOVA test and the Bonferroni test. Results: The results showed that Nano-HAP had the highest mean values of MH (157.699 kg/ mm2), Ca (50.108), and P (24.840) followed by BAG (MH=147.769 kg/ mm2, Ca=47.408, P=22.285), and the lowest mean value was found in the control group (MH=52.299 kg/ mm2, Ca=35.291, P=17.228). Bonferroni's and Tukey's HSD test showed higher significant difference (p<0.05) from demineralization to remineralization phase in all groups, except when compared control group with WSL (Demineralization) showed non-significant difference (P>0.05). Conclusion:all tested agents have highly signif-icant remineralizing potential. Nano-HAP has the highest potential for remineralizing initial enamel caries lesions